2018
DOI: 10.1039/c8cp04492a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating molecular order in nematic liquid crystal capillary bridgesviasurfactant adsorption: guiding principles from dissipative particle dynamics simulations

Abstract: Effect of surfactant tail length on the orientation of liquid crystals is investigated with dissipative particle dynamics (DPD) simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The molecular models utilized here are taken from our previous work. 27 The simulations are conducted in a coarse-grained framework. For example, one water bead (W) represents five water molecules.…”
Section: Molecular Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular models utilized here are taken from our previous work. 27 The simulations are conducted in a coarse-grained framework. For example, one water bead (W) represents five water molecules.…”
Section: Molecular Modelsmentioning
confidence: 99%
“…We quantified the effect of amphiphiles morphological differences on the LC anchoring. 27 The results showed that varying the number of hydrophilic coils and hydrophobic rods in such a model surfactant can largely affect LCs' anchoring alongside surfactant tail-LC interactions. Those results depend on the internal elasticity, which tends to preferentially align the director along the axis of the cylinder.…”
Section: Introductionmentioning
confidence: 98%
“…Details regarding the models implemented for describing water and LC mesogens are reported elsewhere. 31,32 In short, in our coarse-grained representation, one water 'bead', indicated with W in what follows, represents 5 water molecules (i.e., the degree of coarse graining was set equal to 5). The LC mesogens are rod-like molecules composed of 6 beads connected with a harmonic spring.…”
Section: Nanoparticles and Liquid Crystal Mesogensmentioning
confidence: 99%
“…In our implementation, r 0 = 0.6, θ 0 = 180°, k bond = 100k B T/r 2 , and k angle = 100k B T. These parameters yield rather rigid LC molecules, whose phase diagram in the bulk was described elsewhere. 31…”
Section: Nanoparticles and Liquid Crystal Mesogensmentioning
confidence: 99%
See 1 more Smart Citation